Accelerating SMES Performance in East Surabaya through Digitalization - Majid, Nurkholish; Kusuma Wardhani, Nuruni Ika; Fitriyah, Zumrotul (Institute of Computer Science (IOCS), 2024)
Purpose of this research are analyzing impact digitalization among the SMES in Surabaya City by using digital technology which measuring by their perception ease of use, usefulness and trust using digital technology and its impact on SMES Performance. Research conduct with quantitative analysis by using explanatory research design. The population of this research are 7158 SMES in Surabaya especially East Surabaya then we acquired 100 sample of SMES by using Slovin-Formula. Data collected by share questioner among 100 Respondents of SMES in East Surabaya. Data analyzed by using SEM-PLS with instrument validity and reliability test then bootstrapping to know hypothesis-testing results. Results identified perceived ease of use and usefulness affect SMES performance and can improve productivity by using digitalization technology. However, trust has no impact on SMES Performance in Digitalization Technology Context. This study offers significant advantages for the government, particularly in Surabaya City, aiming to enhance digitalization among SMEs by leveraging social media and e-wallets, thereby improving their technological performance. Additionally, it sheds light on how SMEs can harness digitalization technology to increase profitability and reap numerous benefits.